2021
DOI: 10.1098/rspb.2021.1045
|View full text |Cite
|
Sign up to set email alerts
|

Why don't all animals avoid inbreeding?

Abstract: Individuals are expected to avoid mating with relatives as inbreeding can reduce offspring fitness, a phenomenon known as inbreeding depression. This has led to the widespread assumption that selection will favour individuals that avoid mating with relatives. However, the strength of inbreeding avoidance is variable across species and there are numerous cases where related mates are not avoided. Here we test if the frequency that related males and females encounter each other explains variation in inbreeding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 67 publications
1
23
0
Order By: Relevance
“…Analysis of 41 species from six classes indicated that inbreeding avoidance is very general and depends on the risk of inbreeding depression in the species (Pike et al, 2021). Some species have a preference for inbreeding, cichlid fish Pelvicachromimis taeniatus (Thünken et al, 2007) and ground tit Parus humilis (Wang and Lu, 2011) are examples.…”
Section: Avoidancementioning
confidence: 99%
“…Analysis of 41 species from six classes indicated that inbreeding avoidance is very general and depends on the risk of inbreeding depression in the species (Pike et al, 2021). Some species have a preference for inbreeding, cichlid fish Pelvicachromimis taeniatus (Thünken et al, 2007) and ground tit Parus humilis (Wang and Lu, 2011) are examples.…”
Section: Avoidancementioning
confidence: 99%
“…Inbreeding can negatively affect populations by increasing homozygosity and thereby the expression of deleterious recessive alleles, potentially leading to a reduction in fitness that is commonly referred to as inbreeding depression (Charlesworth & Charlesworth, 1999 ; Keller & Waller, 2002 ). These effects may select for various mechanisms of inbreeding avoidance in wild populations (Pusey & Wolf, 1996 ), although the prevalence and strength of such mechanisms are highly variable across species and are largely contingent on historical, demographic, and ecological factors (de Boer et al, 2021 ; Duthie & Reid, 2016 ; Pike et al, 2021 ). Inbreeding avoidance mechanisms include active mate choice mediated by kin‐recognition, delayed maturation or reproductive suppression, extra‐pair or extra‐group copulations, and sex‐biased dispersal (Pusey & Wolf, 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature reviews and meta‐analyses suggest that inbreeding avoidance might not be prevalent in wild populations and that unbiased mating with regard to kinship appears widespread across several animal taxa (de Boer et al, 2021 ; Pike et al, 2021 ). However, as inbreeding depression seems more frequent in smaller or isolated populations (Crnokrak & Roff, 1999 ), mechanisms to avoid incestuous mating are more likely to be found under such circumstances (see e.g., Pike et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations